The difference in density along the bamboo culms of Gigantochloa scortichinii and Bambusa vulgaris - Anokye, Rogerson; Bakar, Edi Suhaimi; Abare, Alhassan Yakubu; Kalong, Regina Maria; Muhammad, Atiku (2014)
Bamboo has good potential to substitute wood-based materials especially in wood-based composite industry. Apart from being fast growing, bamboo also has a good mecahnical properties. Malaysia has a few bamboo species that can be utilised commercially. It was used in terms of traditional purposes and many other countries have also used bamboo as a material in wood-composite industry. For Malaysian bamboo to be accepted as a construction material in the furniture industry, basic properties as density need to be studied. This study was carried out to ascertain the density difference along the culm of the two most common local bamboo species - Gigantochloa scortechinii and Bambusa vulgaris. The study was based on the internodes and nodes sections and along the culm height. A 20 x 20 x thickness (mm) internode and node strips were used. The dried samples were determined for their mass and volumes. The results showed that, for both species, the density increased along the culm with no significant diferences among the sections of nodes and internodes. The results from both species also revealed similar densities with a highest difference of 0.08g/cm3. It was therefore concluded that the two species can be worked and used together where density is the paramount determinant for use.